Ultraestructura del testículo y epidídimo del tepezcuinte, Agouti paca (Rodentia: Dasyproctidae) - Pashov Nicheva, Blagovesta; Matamoros Hidalgo, Yolanda (Revista de Biología Tropical, 1994)
The germ cells observed at MET in the seminiferous tubes of the paca (Agouti paca) are: A and B spermatogonias, primary spermatocites, spermatids and Sertoli cells. The epididymus epithelium is constituted by basal, principal and clear cells.